AB0818-HPR Doctors and nurses do not share the same vision regarding the future role of a specialised nurse. (23rd January 2014) - Ioan, C.; Berghea, F.; Vasile, D.; Predeteanu, D.; Nastase, D.; Otoiu, L.; Kis, E.; Ursa, E. M.; Ciupa, R.; Ciotoroiu, E.; Ionescu, R.
Abstract : Background: We can see how in the last 10-15 years the medical industry has changed (forced by major economical constrains but also by the democratization of the medical information). Both in hospitals and in small clinics the management tend to move responsibilities from the shoulders of the doctors (better paid) to those of (specialized) nurses (and so to reduce the costs). Just a small number of nurses and doctors are involved in such decisions that have a much wider impact. Once the tasks are relocated the system seems to go ahead but how smooth? Do the nurses consider them capable of new challenges? Are them happy with such decision? Do the doctors fully trust their "new" specialized nurses? Objectives: To evaluate the difference between nurses and doctors opinions regarding the future role of rheumatology nurse. Methods: In a focus group exercise we identified the main tasks associated in present with a rheumatology nurse in a specialized hospital. In a literature review we identified additional tasks a rheumatology nurse has to fulfill in various European and US settings. A Survey-Monkey questionnaire was developed to evaluate nurses' and doctors' opinion regarding each of these tasks; nurses ad doctors from 8 rheumatology wards answered on a Likert scale (from 1 to 10 or 1 to 4). Data was analyzed by using SPSS 16.0 software package. Results: A number of 29 doctors and 36 nurses answered the questionnaire. In many cases doctors and nurses agreed (p<0.05) on the tasks a rheumatology nurse can perform: help in minimal invasive procedures, recognition of drugs adverse reactions, recognition of signs and symptoms of a flare, minimal pain management, scoring. More interesting we found domains with large discrepancy between doctors and nurses. The discrepancy index was computed as the difference between the mean opinions of the nurses (marked on 1 to 4 Likert scale) subtracted from the mean opinion of the doctors. Nurses believe they can do but doctors don't agree: investigators in clinical trials (-2.4), review literature (-2.1), propose a pain therapy (-1.7). Nurses believe they can't but doctors believe the nurses could: be involved in musculoskeletal ultrasonography (+2.1), be involved in patient education (+2.1), manage better discussion with a patient with intimate problems (+ 1.7) and help the patient to change the life style (+ 1.6). Additional analyses have been made in sub-groups. Conclusions: The study revealed a great need for discussions between doctors, nurses and management in order to ensure the nurses receive doable tasks and doctors accept without any doubt the results. The study also revealed in what areas both doctors and nurses need to be more updated with positive (and, why not? negative) experiences of involving nurses in activities normally attributed to doctors; EULAR could play an important role in this kind of dissemination. Disclosure of Interest: None Declared